Endodontology at a glance - Davies, Alix; Foschi, Federico; Patel, Shanon (At a glance series, 2018)
"A practical and colourful introductory guide, Endodontology at a Glance covers all the essential topics (diagnosis, endodontic therapy, pain management and outcome of treatment) as well as the recent developments that comprise the field of endodontology. Written by experts in the field, the book explores the causes and sequelae of endodontic disease and offers suggestions for taking an effective patient history. New addition to the At a Glance series covering a core area of dentistry Review style makes for the ideal revision companion Includes access to a companion website with MCQs for self-assessment and downloadable images for use in teaching"...Provided by publisher